A new primary health-care system in the Syrian opposition territories: Good effort but far from being perfect - Alsaied, Tarek; Mawas, Abdullah; Sayah, Fatima Al; Kental, Abdulrazzak; Saqqur, Maher (Avicenna Journal of Medicine, 2017)
Objectives: The primary health-care system in Syria has suffered a great deal of damage over the past 6 years. A large number of physicians and health-care providers have left the country. The objectives of this study are to describe our experience in establishing a primary health-care system in the opposition territories (OTs) in Syria and report the most common treated diseases. Methods: The administrative databases of ten primary care centers in the OT from January 2014 to December 2015 were reviewed. All patients' encounters, including children and adults, in these centers were included in the study. Results: Within the study period, the ten centers served 46,039 patients encounter per month (and average of 4600 patients encounters per center per month). A high number of communicable diseases were noted. Cutaneous leishmaniasis was the most common communicable disease (1170 cases a month). Tuberculosis was treated in 14 patients a month. Other infectious diseases that were almost eradicated before the crises were seen increasingly (29 mumps cases/month, 6 measles cases/month, and 34 cases of typhoid fever/month). Conclusion: The primary health-care system in Syria has been greatly damaged, and tremendous efforts are ongoing to provide access to various basic health-care services including primary care services. Despite these efforts, the current system is very vulnerable and not sustainable. This study summarizes basic health services provided by primary health-care centers in Syrian OTs.
Keywords: Medical relief; primary care; Syrian conflict